Development of ecological settlements in the conditions of organic agriculture as a direction of using the potential of renewable energy sources in Ukraine - Горб, О. О.; Чайка, Т. О.; Яснолоб, І. О. (Scientific Progress & Innovations, 2017)
The relevance of the development of organic agriculture was substantiated in the article. The general requirements and conditions for its maintenance are specified. The necessity of the development of organic farming in Ukraine is proved, which in turn will contribute to the creation and efficient functioning of ecological settlements. The essence of ecological settlements in general and their features in the present conditions are determined. The foreign experience of organization of ecological settlements is studied and possible directions of its adaptation to domestic conditions are formed. Preconditions and peculiarities of formation, development and effective functioning of ecological settlements in Ukraine are presented.